An organoantimony nitrate complex with azastibocine framework as water tolerant Lewis acid catalyst for the synthesis of 1, 2‐disubstitued benzimidazoles. (29th July 2020) - Zhou, Cong; Lei, Jian; Liu, Yongping; Au, Chak‐Tong; Chen, Yi; Yin, Shuang‐Feng
Abstract : A novel organoantimony complex of 6‐cyclohexyl‐6, 7‐dihydrodibenzo[ c, f ] [ 1, 5 ]azastibocin‐12(5H)‐yl nitrate (2 ) was synthesized and systematically characterized by techniques such as NMR spectra, TG‐DSC, and X‐ray diffraction. It was found that the complex 2 exhibits relatively strong Lewis acidity (3.3 < Ho ≤ 4.8) and could be employed as a water tolerant Lewis acid catalyst for the synthesis of synthetically valuable benzimidazole derivatives starting from aldehydes and arylenediamines. This catalytic system shows excellent tolerance toward a wide variety of functional groups, such as methyl, methoxyl, fluoro, chloro, bromo, nitro, cyan, trifluoromethyl, 1‐naphthaldehyde, furfural and n ‐butyl, together with facile reusability in 5 times scale enlarged synthesis. Abstract : A novel organoantimony nitrate complex with azastibocine framework was synthesized and employed as a water tolerant Lewis acid catalyst for the synthesis of synthetically valuable 1, 2‐disubstitued benzimidazoles starting from aldehydes and arylenediamines.